Education Racial and Gender Disparities in COVID-19 Worry, Stress, and Food Insecurities across Undergraduate Biology Students at a Southeastern University - Kelly M. Correia; Shannon R. Bierma; Sophia D. Houston; Madison T. Nelson; Khushwant S. Pannu; Chase M. Tirman; Randi L. Cannon; Lauren R. Clance; Dawn N. Canterbury; Angela N. Google; Blair H. Morrison; Jeremiah A. Henning (Journal of Microbiology & Biology Education, 2022)
ABSTRACT The global spread of the novel coronavirus first reported in December 2019 led to drastic changes in the social and economic dynamics of everyday life. Nationwide, racial, gender, and geographic disparities in symptom severity, mortality, and access to health care evolved, which impacted stress and anxiety surrounding COVID-19. On university campuses, drastic shifts in learning environments occurred as universities shifted to remote instruction, which further impacted student mental health and anxiety. Our study aimed to understand how students from diverse backgrounds differ in their worry and stress surrounding COVID-19 upon return to hybrid or in-person classes during the Fall of 2020. Specifically, we addressed the differences in COVID-19 worry, stress response, and COVID-19-related food insecurity related to race/ethnicity (Indigenous American, Asian/Asian American, black/African American, Latinx/Hispanic, white, or multiple races), gender (male, female, and gender expressive), and geographic origin (ranging from rural to large metropolitan areas) of undergraduate students attending a regional-serving R2 university, in the southeastern U.S. Overall, we found significance in worry, food insecurity, and stress responses with females and gender expressive individuals, along with Hispanic/Latinx, Asian/Asian American, and black/African American students. Additionally, students from large urban areas were more worried about contracting the virus compared to students from rural locations. However, we found fewer differences in self-reported COVID-related stress responses within these students. Our findings can highlight the disparities among students’ worry based on gender, racial differences, and geographic origins, with potential implications for mental health of university students from diverse backgrounds. Our results support the inclusion of diverse voices in university decisioning making around the transition through the COVID-19 pandemic.